Engineering location-based services in the web - Gordillo, Silvia Ethel
In this chapter, we will present a modular approach for building evolvable location- based services in the context of Web applications. We first motivate our research by discussing the state of the art of location-based services; next we analyze which design problems we face while building this kind of application, stressing those problems related with the application's evolution. We present an object-oriented design approach for engineering location-based applications that effectively supports the evolution of these applications rather than their revolution and give a few examples of its use. We finally discuss some further research issues not explicitly addressed in this chapter.